Heritage and the Web : a study of the National Archives of Singapore's first online exhibition. - Leo, Siew Ere. (2008)
This project surveys the National Archives of Singapore's first online exhibition "Colours in the Wind: Old Hill Street Police Station in Retrospect" in terms of its usefulness, usability and impact on learning.